Research on multi-condition and multi-objective control of pumped storage unit optimized by improved multi-objective particle swarm optimization algorithm - Jiang, Xiaoping; Xiu, Tianning; Yu, Hao (Journal of physics. Conference series, 2024)
In order to maintain good control quality of the pumped storage unit regulation system during the switching of operating conditions, a multi-objective optimization framework based on improved multi-objective particle swarm optimization algorithm is proposed, which takes into account the control stability, rapidity and robustness under multiple working conditions. Firstly, the fractional order PID controller with higher applicability and flexibility is introduced to replace the traditional PID controller. Then, an objective function considering the ITAE index of low-head and medium-high-head conditions is constructed. On this basis, the multi-objective particle swarm optimization algorithm with pigeon swarm search operator, adaptive Cauchy mutation strategy and improved initialization method is used to optimize the controller parameters, and the multi-condition and multi-objective fractional order PID optimal control of pumped storage unit regulation system is realized. Through simulation, it is proved that the controller parameters based on the framework optimization proposed in this paper have strong adaptability and robustness under different working conditions, which provides a new idea for the optimal control of pumped storage unit regulation system.